ACCOUNTING SYSTEM OF THE MSMES OF NORTH EAST INDIA - PERFORMANCE ASSESSMENT, TRENDS, GROWTH, CHALLENGES, AND POLICY PERSPECTIVES - Mrs PAYEL BISWAS , (IJRDO - Journal of Business Management, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have a significant contribution towards the economic development of North East India by providing employment opportunities, facilitating entrepreneurship, and enabling inclusive advancement of the region. The effectiveness of MSMEs is considerably decided by the state of their accounting systems, effectiveness of their accounting practices, and regulatory compliance achievements. The objective of this study is to analyze the accounting systems of MSMEs in the North Eastern part of India with regard to performance assessment, emerging trends, and difficulties OPs statirs. The review compiles evidence from recent literature, government reports, and policy documents directed at assessing the adoption of digital accounting technologies, GST accounting, cloud accounting technologies, and financial management in the case of MSMEs. The analysis indicates some persistent barriers, such as financial literacy, lack of accounting skills, low adoption of digital accounting technologies, infrastructural issues, lack of access to formal finance, and varying levels of regulatory compliance levels across the region. The active government projects, including Digital India, Udyam Registration, and MSME Competitive (LEAN) Scheme reflect the tangible movement toward an establishment of technology-based accounting systems. This research concludes that good accounting systems can lead to better performance in finance, ensuring creditworthiness, proper taxation, effective business decisions by management, and enhancing the sustainability of business in the long run. Policy recommendations have been put forward, emphasizing skill development in accounting, using digital technology in accounting, having better affordable accounting tools, and training in accounting specific to the region under study The paper informs researchers, other interested parties, and policy-makers on how to enhance financial governance and business development in the northeast of India.